Anna, Banana, and the big-mouth bet - Rissi, Anica Mrose (Rissi, Anica Mrose. Anna, Banana, 2015)
After telling her dog Banana about her loose tooth and discovering that some of her friends do not believe in the Tooth Fairy, Anna makes an impulsive bet with a pesky boy who also has a loose tooth.